The role of working women in social mobility in Spain - Perales, II. M. and Espino, J.M.G. (International Sociology Review)
This article addresses what is still an under-examined issue in social mobility literature: the role played by women in the transmission of social advantages and life chances. We include models that incorporate both progenitors for those who were born in Spain between 1926 and 1976. We selected this country due to the far-reaching transformations experienced there for the female population in recent decades in terms of fertility rates, labor market, and educational mobility. Our results show that joint models that consider the influence of both the mother$1 (Bs and father$1 (Bs social class more accurately predict children$1 (Bs social mobility than models that only considers the father$1 (Bs social class. Contrary to previous studies, we do not find a clear movement toward a more open society, but rather a gendered fluctuation. While the social fluidity of sons has remained constant over time, daughters have experienced an intense process of social fluidity.- Reproduced s
Keywords: Social class, Social fluidity, Social mobility, Working mothers